Bangladeshi ready‐made garment development via ubiquitous and mobile computing. Issue 4 (22nd January 2021) - Ahad, Taimur; Busch, Peter; Blount, Yvette; Picoto, Winnie
Abstract: Little is known about mobile‐based information system (hereafter MbUS) affordances in the manufacturing sector, particularly in the Bangladeshi ready‐made garment (hereafter RMG) industry ‐ the major contributor to the national economy. However, the sector faces challenges in communication, worker disempowerment, and long lead times to produce finished goods. Research suggests that MbUS has potential development impact to improve communication, co‐ordination, and empowerment. This study narrows the gap through utilizing affordance theory as a theoretical lens to examine MbUS affordance applied to Bangladeshi RMGs. Using 39 interviews, this research explores five MbUS affordances ‐ connectivity, mobility, agility, empowerment and governance, and their relationship to Bangladeshi RMGs. Furthermore, we identify empowerment as a crucial affordance rarely identified in prior RMG literature. Our findings have potential value to RMGs, government, and mobile telecommunications.